2016
DOI: 10.1111/vco.12213
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic detection of canine mammary gland tumours after oral administration of 5‐aminolevulinic acid

Abstract: 5-Aminolevulinic acid (5-ALA) is widely used in photodynamic detection (PDD) and therapy. We evaluated the pharmacokinetics of 5-ALA-induced porphyrins and its effectiveness in PDD in dogs with mammary gland tumours (MGTs) following oral administration. Healthy dogs and those with MGTs (nine each) were orally administered 4 mg kg 5-ALA. Protoporphyrin IX (PpIX) was not detected in the plasma of healthy dogs but it peaked in dogs with MGT at 2 h after 5-ALA administration. In the PDD study, 16 dogs with MGT wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…In the present study, we did not have a direct comparison for the fluorescence intensity of PpIX of each tumor tissue. However, we previously reported that cell density strongly correlated with PpIX photon counts of mammary gland tumor tissue in dogs [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we did not have a direct comparison for the fluorescence intensity of PpIX of each tumor tissue. However, we previously reported that cell density strongly correlated with PpIX photon counts of mammary gland tumor tissue in dogs [17].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, few reports are available on the clinical evaluation of PDD and PDT using 5-ALA in veterinary medicine, although we recently reported that 5-ALA-PDD might serve as an effective detection tool for canine mammary gland tumors [17]. Several studies have also addressed the efficacy of 5-ALA-PDT to treat feline superficial squamous cell carcinoma, reporting 85% complete remission and 51–64% local recurrence [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively little work has been done on translating human PDD to veterinary surgery. Veterinary examples include intraoperative cancer imaging and staging in dogs (Knapp et al, 2007, Cabon et al, 2016, Osaki 2016, and image-giuded surgery in cats (Wenk et al, 2013). The next generation of agents for photodiagnosis are generally based on near infra-red dyes, which allow deeper views into tissues, sometimes complexed with tumour-targeting peptides or antibodies (Luo et al, 2011, Wenk et al, 2013.…”
Section: Photosensitisers For Diagnosismentioning
confidence: 99%
“…The fluorescent dye 5-aminolevulinic acid (5-ALA) has been used to improve the quality of surgery by increasing the extent of resection of high-grade astrocytomas and glioblastoma multiforme. 13,14 Although the successful use of 5-ALA has already been reported in dogs with mammary gland tumors, 15 the same technique may not be suitable for animals with brain tumors because the dye must be orally administered to patients several hours prior to surgery. Another type of fluorophore currently in use during neurosurgery in humans is fluorescein sodium (FS).…”
Section: Introductionmentioning
confidence: 99%